Повышение точности узкодиапазонных импедансометрических каналов прямого преобразования - Мельник, В.Г.; Семенычева, Л.Н. (Технічна електродинаміка, 2011)
The paper deals with the results of researches of precision measurement channel, which is based on the AC bridge circuit with integral digital to analogy converter and an indicator of balance, which includes high-sensitivity integratingtype analogy to digital converter such as MAX132. Results of researches of the linearity characteristics of the transformation of the channel are given, its specific error are discussed. The ways of significantly reducing the errors caused by the nonlinearity characteristics of the ADC are proposed.